2022
DOI: 10.1002/adfm.202204462
|View full text |Cite
|
Sign up to set email alerts
|

Lipid‐Polymer Hybrid “Particle‐in‐Particle” Nanostructure Gene Delivery Platform Explored for Lyophilizable DNA and mRNA COVID‐19 Vaccines

Abstract: SARS‐CoV‐2 has led to a worldwide pandemic, catastrophically impacting public health and the global economy. Herein, a new class of lipid‐modified polymer poly (β‐amino esters) (L‐PBAEs) is developed via enzyme‐catalyzed esterification and further formulation of the L‐PBAEs with poly( d , l ‐lactide‐coglycolide)‐ b ‐poly(ethylene glycol) (PLGA‐PEG) leads to self‐assembly into a “particle‐in‐particle” (PNP) nanostructure for gene delivery. Out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…We then explored the long-term storage capability of AA3-DLin LNPs under different storage conditions. Sucrose was formulated into AA3-DLin LNP as the cryoprotectant to stabilize LNP structure during storage. , Previous reports showed that sucrose was the most effective cryoprotectant with high viscosity and low molecular mobility, and serves as a stabilizer to minimize the van der Waals interaction and preserve the spacing between the nanoparticles during frozen storage. ,, A sucrose solution was added to LNPs with final concentrations of 0–40 wt % and the resulting LNPs were further lyophilized as dry powder or stored at 4 °C and −20 °C with a timeline of 12 months. The transfection efficacy of stored LNPs was characterized in vitro and in vivo with the fresh LNPs as the positive control.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We then explored the long-term storage capability of AA3-DLin LNPs under different storage conditions. Sucrose was formulated into AA3-DLin LNP as the cryoprotectant to stabilize LNP structure during storage. , Previous reports showed that sucrose was the most effective cryoprotectant with high viscosity and low molecular mobility, and serves as a stabilizer to minimize the van der Waals interaction and preserve the spacing between the nanoparticles during frozen storage. ,, A sucrose solution was added to LNPs with final concentrations of 0–40 wt % and the resulting LNPs were further lyophilized as dry powder or stored at 4 °C and −20 °C with a timeline of 12 months. The transfection efficacy of stored LNPs was characterized in vitro and in vivo with the fresh LNPs as the positive control.…”
Section: Resultsmentioning
confidence: 99%
“…A CALB enzyme-catalyzed esterification was utilized to synthesize ionizable cationic lipids between hydroxyl groups (−OH) of amino alcohol and carboxylic acid groups (−COOH) of lipid acids. , Briefly, amino alcohol was dissolved in THF using two-neck round-bottom flask, and then 0.5 g of amino alcohol was added and dissolved in 5 mL of THF followed by the addition of 2 molar ratio excess of lipid acid and 0.5 g of CALB. The reaction lasted for 72 h with the protection of nitrogen at 60 °C.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prepared SiO 2 nanoparticles were immediately modified with PEI (V-SiO 2 -P), mRNA loading followed by the addition of a complete LB coating (V-SiO 2 -P/LB; The thickness of LB is 7-10 nm; Red arrow). The two steps of PEI and LB modifications could improve the mRNA binding efficiency, facilitate lysosomal escape, and maintain colloidal stability that is capable of effectively avoiding mRNA degradation (Wang et al, 2018) (Noureddine et al, 2020) (Xia et al, 2009;Wang et al, 2018) ( Noureddine et al, 2020;Gao et al, 2021;Riley et al, 2021;Li et al, 2022). At present, there are few studies on mRNA delivery by inorganic nanomaterials, and LNPs have been an effective mRNA delivery (Meng et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Second, their biomimetic morphology enhances gene delivery efficiency both in vitro and in vivo. Finally, a supported LB coating maintains colloidal stability and effectively prevents mRNA degradation (Noureddine et al, 2020;Gao et al, 2021;Riley et al, 2021;Li et al, 2022). Using green fluorescence protein (GFP)-expressing mRNA as a model, the intracellular delivery and transfection efficiency of m@V-SiO 2 -P/LB nanoparticles were demonstrated to be much higher than that of the benchmark LNPs loaded with mRNA (m@LNPs).…”
mentioning
confidence: 99%